Study of genetic basis of resistance to leaf rust isolates in durum wheat - Del Olmo A.I.; Sillero J.C.; Marone D.; Matteu L.; Mastrangelo A.M.; Rubiales D. (Cereal science and technology for feeding ten billion people: genomics era and beyond, 2008)
In the present work a phenotipical and molecular marker-based approach is described, in an attempt to unravel the genetic basis of the postulated durable resistance to leaf rust in durum wheat cv. Creso. A recombinant inbred line (RIL) population (F6:7) was developed by crossing durum wheat cvs Creso (resistant) and Pedroso (susceptible). Resistance evaluation of lines suggests that durable resistance of Creso could be due to the combination of different mechanisms with distinct genetic basis. A molecular mapping approach is in course in order to individuate chromosomic regions involved in control of these mechanisms: more than 300 microsatellite PCR-based markers have been tested on parental lines, all with a known position on the wheat genome. About 30% of them were found polimorfic between Creso and Pedroso.
Meeting of the Eucarpia Cereal Section, 2006/11/13-17, Lleida (Spain)